2012
DOI: 10.1007/s00438-012-0685-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression profile in PBMCs from subjects with AERD and ATA: a gene marker for AERD

Abstract: Aspirin-exacerbated respiratory disease (AERD) is associated with severe asthma and aspirin can cause asthma to worsen, often in the form of a severe and sudden attack. The oral aspirin challenge is the gold standard to confirm the diagnosis of AERD, but it is time consuming and produces serious complications in some cases. Therefore, more efficient and practical method is needed to predict AERD patients. The aim of the present study was to identify AERD-related gene expression in peripheral blood mononuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
(34 reference statements)
2
17
1
Order By: Relevance
“…We also identified 8 genes with differentially methylated CpG sites in AECs derived from asthmatic compared to AECs obtained from atopic children. Although gene markers in PBMCs have been identified through gene expression analysis for multiple diseases including aspirin-exacerbated respiratory disease and asthma [35], [36], we did not identify any differences in DNA methylation when comparing PBMCs from the three subject groups.…”
Section: Discussioncontrasting
confidence: 67%
“…We also identified 8 genes with differentially methylated CpG sites in AECs derived from asthmatic compared to AECs obtained from atopic children. Although gene markers in PBMCs have been identified through gene expression analysis for multiple diseases including aspirin-exacerbated respiratory disease and asthma [35], [36], we did not identify any differences in DNA methylation when comparing PBMCs from the three subject groups.…”
Section: Discussioncontrasting
confidence: 67%
“…Deep sequencing studies can also be performed. In this sense, a recent genome-wide methylation study on nasal polyps found a differential pattern in patients with NSAID-induced DHRs [133], and a set of 2 gene markers has been proposed to discriminate NERD from aspirin-tolerant asthma [134]. Exome sequencing has also been used to identify variants associated with hypersensitivity to NSAIDs [135].…”
Section: Further Approaches For Deciphering Dhrsmentioning
confidence: 99%
“…Administration of annexin protein prior to an ovalbumin challenge significantly reduced airway hyperresponsiveness, attenuated the production of inflammatory cytokines, such as IL-4, IL-5, and IL-13, as well as ovalbumin-specific IgE in a mouse model of asthma [48]. Meanwhile, neuroactive ligand-receptor interaction, which is another enriched pathway, was reported as a significantly enriched pathway in a differential gene expression study with AERD and ATA subjects [49]. Therefore, we suppose the major modules in the integrated network can play an important role in the pathways related to the treatment of AERD.…”
Section: Resultsmentioning
confidence: 99%